The Repercussions of Covid-19 Pandemic on Urban Environments - Al-Qusaybati, Nada (Journal of Architecture and environment of child, 2022)
Urbanization is one of the great achievements of modern societies. Civilization has produced large cities with dense populations as they offer jobs opportunities, services, and a better quality of life. Later, it was revealed that these cities, despite their development, were unable to protect their residents from the spread of diseases and epidemics. This calls for rethinking urban planning standards to design healthy cities that improve the health of the population and reduce the spread of disease. During the past two years, the health crisis caused by the Corona virus turned into a dangerous epidemic that swept the entire world and had a great impact on all aspects of life, such as health, education, transportation, economy, and social communication. This paper reviews some recent studies that are related to Covid-19 pandemic and focuses on the impact of this pandemic on urban environments, through four main aspects: public spaces, transportation, global communication, and digital programs. These aspects conclude with some proposals for designing safer urban spaces, which help reduce Spread of diseases and secure more protection for the residents. The research proposals may be insufficient or effective in the long term because the current crisis is still ongoing, and its consequences are still unknown. Currently, it is impossible to predict the future of cities after the pandemic. On the one hand, medicine could end this pandemic then the cities would be able to return to their normal activity and prosperity. On the other hand, the virus may continue mutates, with the possibility of the emergence of more virulent viruses, which